Kegiatan Rencana Perlindungan dan Pengelolaan Sumber Daya Air Di Kabupaten Bintan - Ira Mughni Pratiwi,; Ika Arsi Anafiati, (ReTII, 2022)
Water is one of the most important natural resources that man cannot live without, plays an important role in public welfare, and become main capital and factor for development. Over the years, inequality of water distribution is one of the most pressing challenges. Climate change is already affecting water availability. The aim of this public service is for making plans the protection and management of water resources in Bintan Regency. Research method in Bintan Region, chiefly of water resources aspect are survey, questionnaires or interviews, public participation. Rivers of Bintan Regency are mostly narrow and shallow for inland waterways transportation. The rivers as a wetland provide source for water discharge from swamps and surroundings. Source of community water needs is supplied by springs occurs, reservoir water, and water from post mining lake. Groundwater potential in Bintan Regency is sufficient and its yield in term of excellent quality, especially the deep groundwater. Most of Bintan Regency surface water comes from some area be capable of infiltrating, reserving, and collecting the water. Effort for water resources utilizing and reserving through the conserving and optimal sustainable use of water.